The book of Proverbs in social and theological context - Dell, Katharine 1961- (Cambridge Cambridge University Press, 2006)
The book of Proverbs is the starting point of the biblical wisdom tradition. But how did individual proverbs, instructions and poems come together to form the various collections we have today? Katharine Dell explores the possible social contexts for this varied material in the royal court, wisdom schools and popular culture. She draws shrewdly on materials from the wisdom traditions of the ancient Near East, in particular Egypt, in order to bolster and enhance her theories. She argues that Proverbs had a theological purpose from its conception, with God's creativity being an integral theme of the text rather than one added in later redactions. Dell also shows that echoes of other Old Testament genres such as prophecy, law and cult can be found in Proverbs, notably in chapters 1-9, and that its social and theological context is much broader than scholars have recognised in the past.
Social context(s) in Proverbs 1-9 -- Social context (s) in Proverbs 10:1-22:16 -- Social context(s) in Proverbs 22:17-31:31 -- Mention of Yahweh in Proverbs -- Theological context -- Echoes of other Old Testament texts and contexts in Proverbs
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Bible -- Theology; Bible -- Socio-rhetorical criticism; Bible -- O.T. -- Proverbs. -- Socio-rhetorical criticism; Bible -- O.T. -- Proverbs. -- Theology; Bible ; Proverbs ; Socio-rhetorical criticism; Bible ; Proverbs ; Theology